Role of Substance P and Its Receptor Neurokinin 1 in Chronic Prurigo: A Randomized, Proof-of-Concept, Controlled Trial with Topical Aprepitant - Tatevik Ohanyan; Nicole Schoepke; Stefan Eirefelt; Gert Hoey; Witte Koopmann; Tomasz Hawro; Marcus Maurer; Martin Metz (Medical Journals Sweden, 2017)
Substance P (SP) and its receptor neurokinin 1 (NK1R) are thought to be involved in the pathogenesis of chronic prurigo. Here, we assessed SP serum levels, cutaneous NK1R expression, and the effects of topical aprepitant, an NK1R antagonist, in patients with chronic prurigo. SP and NK1R were increased, compared with controls, in the serum and in lesional vs. non-lesional skin of the patients, respectively. Aprepitant, in a randomized, placebo-controlled, split-sided, doubleblind trial, reduced the intensity of pruritus as assessed by visual analogue scale by >50% from baseline to day 28 (-35.2), but so did placebo vehicle (-38.1, p= 0.76). Overall clinical scores improved significantly by day 28 in both treatment groups, with no significant difference between the 2 groups (p=0.32). Our findings imply that both SP and NK1R are involved in the pathogenesis of chronic prurigo. Parallel groupdesigned trials are needed to assess the efficacy of topical aprepitant treatment in this condition.